Radar RF Circuit Design, Second Edition - Kingsley, Nickolas (Artech House, 2022)
This new edition of a previous bestseller gives you practical techniques for optimizing RF and microwave circuits for applications in radar systems design, with an emphasis on current and emerging technologies. Completely updated with new material, the book shows you how to design RF components for radar systems and how to choose appropriate materials and packaging methods. It takes you through classic techniques, to the state of the art, and finally to emerging technologies. You will learn:How to design high-frequency circuits for use in radar applications; How to integrate components while avoiding higher-level assembly issues and troubleshooting problems on the measurement bench; How to properly simulate, build, assemble, and test high-frequency circuits; How to debug issues with hardware on the bench; How to connect microwave theory to practical circuit design. Theory and practical information are provided while addressing topics ranging from heat removal to digital circuit integration. The book serves as a teaching aid for classic techniques that are still relevant today. It also demonstrates how these techniques are serving as the foundation for technologies to come. You will be equipped to consider future needs and emerging enabling technologies and confidently think (and design) outside the box to ensure future needs are met. The book also shows you how to incorporate modern design techniques often overlooked or underused, and will help you to better understand the capabilities and limitations of today's technology and the emerging technologies that are on the horizon to mitigate those limitations.This is a must-have resource for system-level radar designers who want to up their game in RF/microwave component design. It is also a great tool for RF/microwave engineers tasked or interested in designing components for radar systems. Students and new designers of radar components will also benefit and be well prepared to start designing immediately.